The German-Brazilian Partnership for a Socially Just and Ecological Transformation: Bilateral cooperation as catalyst for the UN climate process - Jule Könneke (Stiftung Wissenschaft und Politik (SWP), 2024)
Growing North-South tensions are impeding global climate cooperation and hampering Germany's search for reliable partners. Brazil is a key actor with the potential to alleviate tensions: it sees itself as a bridge-builder and will host the Climate Change Conference in 2025 (COP30). Under their new Partnership for a Socially Just and Ecological Transformation, Germany and Brazil should work to strengthen confidence in the climate negotiations, and more generally to promote effective North-South cooperation.
Keywords: 320; Germany; Brazil; German-Brazilian relations; Partnership for a Socially Just and Ecological Transformation; President Luiz Inácio Lula da Silva; Global North; Global South; climate policy; UNFCCC; COP30 Belém; COP28 Dubai; Global Stocktake; GST; Nationally Determined Contribution; NDC; Global Governance; climate finance; COP (30 : 2025 : Belém)